Silent Voices: Dwelling with our Specters through Palimpsesto (2017), by Doris Salcedo - Gutiérrez Cajaraville, Carlos; Calonge Conde, Ana (Text Matters: A Journal of Literature, Theory and Culture, 2024)
A palimpsest is a writing erased and replaced by another. Sometimes, perhaps all too often, our lives become incarnated palimpsests thanks to the prevailing biopolitics, which refers not only to the government of the living, but also to the multiple practices of dying and disappearing. Can art teach us to create new spaces of co-habitation with our essential ghosts, with those who refuse to abandon us despite everything? In this article we address the work entitled Palimpsesto, in which the Colombian artist Doris Salcedo (Bogotá, 1958), makes visible one of the most ignominious events in our recent history: the deaths of thousands of people in the Mediterranean due to indifference and, on occasions, the complicity—conscious or unconscious—of a desensitized European society, closed in on itself. In Palimpsesto, the artist creates a space where those absences are permanently present in absentia. However, Salcedo’s art goes beyond testimony and representation: the tears that flow from the earth itself, outlining on the ground the names of women and men who drowned while fleeing war, reveal not only the need to name those who are no longer with us, but could lay the foundations to erect a kind of divinology (Meillassoux, “Deuil à venir” 105) through which new ties and forms of dwelling would be built, beyond interested political use, between human beings and those harassing absences.